Anticancer natural products targeting immune checkpoint protein network. (November 2022) - Chun, Kyung-Soo; Kim, Do-Hee; Raut, Pawan Kumar; Surh, Young-Joon
Abstract: Normal cells express surface proteins that bind to immune checkpoint proteins on immune cells to turn them off, whereby the immune system does not attack normal healthy cells. Cancer cells can also utilize this same protective mechanism by expressing surface proteins that can interact with checkpoint proteins on immune cells to overcome the immune surveillance. Immunotherapy is making the best use of the body's own immune system to reinforce anti-tumor responses. The most generally used immunotherapy is the control of immune checkpoints including the cytotoxic T lymphocyte-associated molecule 4 (CTLA-4), programmed cell deathreceptor 1 (PD-1), or programmed cell death ligand-1 (PD-L1). In spite of the clinical effectiveness of immune checkpoint inhibitors, the overall response rate still remains low. Therefore, there have been considerable efforts in searching for alternative immune checkpoint proteins that may work as new therapeutic targets for treatment of cancer. Recent studies have identified several additional novel immune checkpoint targets, including lymphocyte activation gene-3, T cell immunoglobulin and mucin-domain containing-3, T cell immunoglobulin and immunoreceptor tyrosine-based inhibition motif domain, V-domain Ig suppressor of T cell activation, B7 homolog 3 protein, B and T cell lymphocyte attenuator, and inducible T cell COStimulator. Natural compounds, especially those present in medicinal or dietary plants, have been investigated for their anti-tumor effects in various in vitro and in vivo models. Some phytochemicals exert anti-tumor activities based on immunoregulatioby blocking interaction between proteins involved in immune checkpoint signal transduction or regulating their expression/activity. Recently, synergistic anti-cancer effects of diverse phytochemicals with anti-PD-1/PD-L1 or anti-CTLA-4 monoclonal antibody drugs have been continuously reported. Considering an increasing attention to noteworthy therapeutic effects of immune checkpoint inhibitors in the cancer therapy, this review focuses on regulatory effects of selected phytochemicals on immune checkpoint protein network and their combinational effectiveness with immune checkpoint inhibitors targeting tumor cells.